Zinc–Air Batteries: Atomically Thin Mesoporous Co3O4 Layers Strongly Coupled with N‐rGO Nanosheets as High‐Performance Bifunctional Catalysts for 1D Knittable Zinc–Air Batteries (Adv. Mater. 4/2018). Issue 4 (22nd January 2018) - Li, Yingbo; Zhong, Cheng; Liu, Jie; Zeng, Xiaoqiao; Qu, Shengxiang; Han, Xiaopeng; Deng, Yida; Hu, Wenbin; Lu, Jun
Abstract : Knittable fiber‐shaped zinc–air batteries based on atomically thin mesoporous Co3 O4 layers strongly coupled with nitrogen‐doped reduced graphene oxide nanosheets as bifunctional catalysts of the air electrodes are developed by Cheng Zhong, Yida Deng, Jun Lu, and co‐workers in article number1703657 . They can be fabricated by a quick, facile, and continuous method. These high‐energy‐density batteries can be knitted into clothes and used as the power supply for wearable electronic devices.